2009
DOI: 10.1016/s0025-6196(11)60559-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Predicts Outcomes of Non-Critically Ill Patients

Abstract: In this study, AKI was associated with adverse outcomes in non-critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…It has been shown that the AKIN classification, like the RIFLE classification, allowed the identification and stratification of AKI in a large proportion of hospitalized patients and was independently associated with the outcome [34, 4856]. In fact, patients with AKI had higher in-hospital mortality and longer lengths of stay, and AKI survivors were more likely to be discharged to an extended care facility.…”
Section: The Acute Kidney Injury Network (Akin) Classificationmentioning
confidence: 99%
“…It has been shown that the AKIN classification, like the RIFLE classification, allowed the identification and stratification of AKI in a large proportion of hospitalized patients and was independently associated with the outcome [34, 4856]. In fact, patients with AKI had higher in-hospital mortality and longer lengths of stay, and AKI survivors were more likely to be discharged to an extended care facility.…”
Section: The Acute Kidney Injury Network (Akin) Classificationmentioning
confidence: 99%
“…[1][2][3][4] Even a relatively small degree of renal injury increases a patient's risk of a prolonged hospital stay, chronic kidney disease (CKD), ESRD, and death. 2,[5][6][7][8][9][10] Over the last 2 decades, the incidence of hospitalized AKI has increased dramatically. [11][12][13][14] Precise estimations vary depending on population and method of case identification, but a recent community-based study of AKI estimated the incidence of nondialysis requiring AKI at 522 per 100,000 population per year and dialysis-requiring AKI at 30 per 100,000, 13 which is well over that of ESRD.…”
mentioning
confidence: 99%
“…Volkmann et al [20] demonstrated that AKI may be hidden in over 25% of patients who underwent CABG. Thus, the existence of a classification criterion to detect early kidney as well as a proposal to unify the classification/definition of AKI are essencial [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The term AKI is used to reflect the entire spectrum of what is defined as the abrupt reduction in renal function, in hours or days, in which acute renal failure (ARF) is characterized by a decrease in the glomerular filtration rate and/or urinary volume, in addition to the loss of basic functions, such as the inability to maintain the hydro-electrolyte and basic acid balance [2]. Most estimates demonstrates that over 30% of patients undergoing cardiac surgery develop clinically severe renal damage [3], with the need for dialysis ranging from 1.4% to 7% [4,5] and mortality rate of 5% to 44% [6,7].…”
Section: Introductionmentioning
confidence: 99%